Lattice Boltzmann Method for Reacting Flows in Porous Media (Advances in Applied Mathematics and Mechanics, 2021)
We review recent developments in lattice Boltzmann method for reactingflows in porous media.  We present the lattice Boltzmann approaches forincompressible flow, solute transport and chemical reactions in both thepore space and at the fluid/solid interfaces. We discuss in detail the methodsto update solid phase when significant mass transfer between solids and fluidsis involved due to dissolution and/or precipitation. Applications in differentareas are presented and perspectives of applying this method to a few importantfields are discussed.